Qualitative and Quantitative Analysis for Determination of Glue Snifferas Urine (Global Journal of Science Frontier Research, 2014)
Inhalant abuse is defined as an intentional inhalation of solvents or volatile substances present in materials such as glues and paints. The most commonly abused inhalant today is glue due to low price and easy access. Glue sniffing produces fast and pleasurable sensory experience to the abuser. Quantitative analysis of hippuric acid using UV-Vis at wavelength 417 nm was determined successfully. The results gave a regression coefficient of 0.994. The recovery, accuracy and coefficient variance of hippuric acid were 96.57%, 2.94% and 0.50% respectively. Reversed-phase high performance liquid chromatography using a simple method for the simultaneous determination of hippuric acid and benzoic acid was also described. The chromatography was performed on a Nova-Pak C18 (3.9 x 150 mm) column with a mobile phase of methanol: water: acetic acid (20:80:0.2) using UV detection at 254 nm. The calibration of standards was linear within concentration range of 0.125 to 6.0 mg/mL of hippuric acid and benzoic acid respectively.
Keywords: glue; hippuric acid; color test; ultra violet-visible